2020
DOI: 10.3389/fimmu.2020.00352
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Serotype 2 and Its Non-Structural Proteins 2A and 2B Activate NLRP3 Inflammasome

Abstract: Dengue is the most prevalent and rapidly transmitted mosquito-borne viral disease of humans. One of the fundamental innate immune responses to viral infections includes the processing and release of pro-inflammatory cytokines such as interleukin (IL-1β and IL-18) through the activation of inflammasome. Dengue virus stimulates the Nod-like receptor (NLRP3-specific inflammasome), however, the specific mechanism(s) by which dengue virus activates the NLRP3 inflammasome is unknown. In this study, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 71 publications
(89 reference statements)
0
34
2
Order By: Relevance
“…Pharmacological inhibition of NLRP3, caspase-1 and CRISPR knockout of ASC in endothelial cells showed that NS2A and NS2B mediated inflammasome and IL-1β secretion was NLRP3 and caspase-1 specific. Lastly, the study also suggested that NS2A triggering NLRP3 inflammasome activation is due to Ca ++ homeostasis and/or mitochondrial disruption /ROS production (Shrivastava et al, 2020 ). In summary, these evidences show the dengue virus proteins induced mechanism in activating NLRP3 inflammasome.…”
Section: Response Of Host Inflammasome To Denv Infectionmentioning
confidence: 96%
“…Pharmacological inhibition of NLRP3, caspase-1 and CRISPR knockout of ASC in endothelial cells showed that NS2A and NS2B mediated inflammasome and IL-1β secretion was NLRP3 and caspase-1 specific. Lastly, the study also suggested that NS2A triggering NLRP3 inflammasome activation is due to Ca ++ homeostasis and/or mitochondrial disruption /ROS production (Shrivastava et al, 2020 ). In summary, these evidences show the dengue virus proteins induced mechanism in activating NLRP3 inflammasome.…”
Section: Response Of Host Inflammasome To Denv Infectionmentioning
confidence: 96%
“…It is well established that thrombocytopenia and vascular dysfunction are common manifestations of severe DENV infection. Analysis of human fatal cases and studies in animal models provided evidence that DENV infects endothelial cells lining different tissues [ 18 , 19 , 20 , 21 , 22 ], raising the possibility that microvascular leakage is underpinned by dysregulated endothelial function and/or viral-induced death [ 23 , 24 , 25 ]. A major limitation in understanding the mechanisms underlining those issues is the lack of an immunocompetent mouse experimental model that sustains virus replication and present dengue clinical signs after systemic inoculation.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of a higher level of NLRP3 expression, ASC oligomerization, and Caspase-1 activation from LPS-treated HMEC-1 cells transfected with NS2A or NS2B indicates that NS2A and NS2B can activate IL-1β mediated NLRP3 inflammasome. 135 Above all, results suggest that DENV M, NS2A, and NS2B proteins induce NLRP3 inflammasome activation.…”
Section: Rna Viruses That Activate Nlrp3 Inflammasomesmentioning
confidence: 89%
“… 132 , 133 However, the Nonstructural proteins 2A, 2B, and structural protein M activate the NLRP3 inflammasome. 134 , 135 M protein of DENV is responsible for endothelial dysfunction, and vascular leakage resulting in IL-1β mediated NLRP3 activation. 134 DENV stimulates inflammatory NLRP3 assembly in platelets.…”
Section: Rna Viruses That Activate Nlrp3 Inflammasomesmentioning
confidence: 99%
See 1 more Smart Citation